Header Expressions and What is Attached to it in Pre-Islamic Poetry, a Semantic Study - Susan Karim Farag Jabr Al-Hijami, Researcher; Muhammad Mazal Khalati, Prof Dr. (lark, 2022)
The pre-Islamic poets were able to employ the words of the body in the semantic expression of their poetic purposes. They excelled in drawing pictures and embodying their feelings, thoughts, and the nature of their lives, which were characterized by wars, conflicts, harsh deserts, and permanent migration. Among these terms are (the word head), and what is attached to it, such as skull, head and hair. These words had different connotations; It comes according to the nature of the verbal accompaniment, and according to the context of the house and the poem. In the dictionaries, it became clear to us the triple origin of the word and the meaning that came out to it, then it was followed by different connotations of the same word, and it was used in pre-Islamic poetry that occupied a prominent position, and it was an integrated linguistic wealth.